The Voice of Vedanta in British Romanticism and American Transcendentalism: Perception, Composition and Thought of Wordsworth and Whitman - Priyanka Gupta; Vinod Solanki (Progress in Language, Literature and Education Research Vol. 7, 2024)
Wordsworth and Whitman are the two harbingers of a new era in the literary history of their respective periods. The purpose of the paper is to infuse the words and the works of the two literary maestros who evangelized the innate divinity in every aspect of the resplendent nature- the flora, the fauna and the human beings have been cognized as the living embodiments of the Celestial Powers in the universe. William Wordsworth and Walt Whitman, the seekers of the ultimate truth, are the prime figures of this study. One has been addressed as the paragon of the Romantic Movement, and the other as the visionary poet of the Transcendental Movement. Realizing the Divine self in every creature is when the two come together. The efforts to determine the supernal affinity, as proposed by the two, are likewise synthesized in this study. Preaching the doctrine of universal unity, the prophets declared that the Supraterrestrial Oneness is what endures eternally and that, divisions vanish in the area of eternity. The Vedic philosophy, which holds that realizing one’s unity with the Absolute Transcendent Brahman and overcoming the constraints of self-identity is the ultimate objective of every human being in this cosmos, bears similarities to the notion of oneness among all. The paper, thus, endeavours to raise the voice of the eternal theory of Vedanta through the glory of the Divine in Nature sung by Wordsworth and Whitman alike. Among the pioneers of the Romanticism and the Transcendentalism, the perception, the composition and the thought - currents of William Wordsworth and Walt Whitman are the subject of study in this paper as they saw the unfolding of the Omnipresent and the Omniscient might in each and every aspect of nature. The writings, verses and the personalities of Wordsworth and Whitman have explored the unseen and the unraveled virtuosity with the power of their experiential spirituality. This exploration, by the soul, is the purpose of the Vedanta and the means to discover the same, is the purpose of this paper.